2017
DOI: 10.3892/ol.2017.6543
|View full text |Cite
|
Sign up to set email alerts
|

Management of supratentorial recurrent low-grade glioma: A multidisciplinary experience in 35 adult patients

Abstract: The management of recurrent diffuse low-grade gliomas (LGGs) is controversial. In the present study, the multidisciplinary management of 35 patients with recurrent LGGs was retrospectively analyzed. Tumor progression or recurrence was defined by clinical, radiological and/or metabolic pejorative evolution. All patients were regularly followed up by a multidisciplinary neuro-oncological group at Hôpital Erasme. Patients with histologically confirmed supratentorial LGGs (7 astrocytoma, 22 oligodendrogliomas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…( 35 ), the median time to transformation was significantly prolonged after reoperation (14.4 years) compared with a control group without the second surgery (3.5 years, p = 0.0002) ( 38 ). However, the rate of MT histologically confirmed at reoperation is high, i.e., in a range between 19% and 74% in the literature ( 24 26 , 31 , 35 , 36 , 39 ), with a lesser EOR ( 37 ) and a decreased OS when reoperation is performed after tumor transformation ( 28 ).…”
Section: Why To Reoperate: the Benefit Of Repeat Resection(s) On Long...mentioning
confidence: 97%
See 2 more Smart Citations
“…( 35 ), the median time to transformation was significantly prolonged after reoperation (14.4 years) compared with a control group without the second surgery (3.5 years, p = 0.0002) ( 38 ). However, the rate of MT histologically confirmed at reoperation is high, i.e., in a range between 19% and 74% in the literature ( 24 26 , 31 , 35 , 36 , 39 ), with a lesser EOR ( 37 ) and a decreased OS when reoperation is performed after tumor transformation ( 28 ).…”
Section: Why To Reoperate: the Benefit Of Repeat Resection(s) On Long...mentioning
confidence: 97%
“…( 25 ); 62% of patients still alive following a median FU of 109 months in the study of Spitaels et al. ( 31 ); 92% of patients still alive at 5 years in the study of Capo et al. ( 36 ); and 93.5% still alive after an overall FU of 8.3 years in the study of Ng et al.…”
Section: Why To Reoperate: the Benefit Of Repeat Resection(s) On Long...mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The adjuvant treatment with chemotherapy and radiotherapy can be indicated in cases of recurrence of low-grade gliomas submitted to a second surgery or not. 4…”
Section: Introductionmentioning
confidence: 99%
“…3 The adjuvant treatment with chemotherapy and radiotherapy can be indicated in cases of recurrence of low-grade gliomas submitted to a second surgery or not. 4 For some authors, 5 reoperation for recurrent low-grade glioma is strongly indicated and should be as radical as possible. For others, 6 there is no strong evidence to recommend reoperation, and further clinical studies on the subject are required.…”
Section: Introductionmentioning
confidence: 99%